Russian Certainty of NATO Hostility: Repercussions in the Arctic - Wilhelmsen, Julie; Hjermann, Anni Roth (Arctic Review on Law and Politics, 2022)
How does a security dilemma dynamic between parties deemed not to hold hostile intentions toward each other emerge and escalate? This article investigates Russian official discourse on NATO engagement in Europe post-Crimea (2014), and its impact on security interaction in the Arctic. We also examine how Russia represents NATO intentions and actions in a context seen by Russia as a relation of war. We identify the effect of these changing representations of self and other for the emerging securitization dilemma in relations between Russia and NATO, arguing that they have replaced uncertainty about NATO’s hostile intentions with certainty. Although Russia still articulates the Arctic as a unique cooperative region, there may be little space left for non-conflictual Russian action when encountering NATO in the Arctic. We highlight the agency and importance of evolving political rhetoric in creating a dangerous situation where lethal conflict can occur between parties who do not seek it, and also suggest that adjustments to patterns of official speech could be a tool of mitigation.